Changes in aerobic and anaerobic performance capabilities following different interval-training programs - Meckel, Y.; Sindiani, M.; Ben Zaken, S.; Eliakim, A. (Central European Journal of Sport Sciences and Medicine, 2017)
The aim of the study was to compare the effect of an increasing-distance interval-training program and a decreasingdistance interval-training program, matched for total distance, on aerobic and anaerobic performance capabilities. Forty physical education students were randomly assigned to either increasing- or decreasing-distance interval-training group (ITG and DTG), and completed two similar sets of tests before and after six weeks of training. One training program consisted of 100 - 200 - 300 - 400 - 500 m running intervals, and the other 500 - 400 - 300 - 200 - 100 m. While both training programs led to a significant improvement in 2,000 m run (ES = 0.02-0.68), the improvement in the DTG was significantly greater than in the ITG (18.3 ±3.6 vs. 12.2 ±3.2%, p < 0.05). In addition, while both training programs led to a significant improvement in 300 m run (ES = 0.25-0.73), the improvement in the DTG was significantly greater than in the ITG (21.1 ±1.8 vs. 15.4 ±1.1%, p < 0.05). The findings indicate that beyond the significant positive effects of both training programs, the DTG showed significant superiority over the ITG in improving aerobic and anaerobic performance capabilities. Athletes should acknowledge that, in spite of identical total work, interval-training program might induce different physiological impacts if order of intervals is different.